2022
DOI: 10.1001/jamaoncol.2022.0514
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Etirinotecan Pegol for Patients With Metastatic Breast Cancer and Brain Metastases

Abstract: IMPORTANCEPatients with breast cancer and brain metastases (BM) have a poor prognosis and high clinical need for novel treatments; however, historically, studies have often excluded these patients. Although the BEACON study did not meet its primary end point, treatment with etirinotecan pegol vs chemotherapy of the physician's choice for patients with advanced breast cancer demonstrated a significant improvement in overall survival (OS) for the prespecified patient subgroup with preexisting, pretreated, and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In the BEACON trial (a phase III trial), BCBM patients who received NKTR-102 treatment had a markedly lowered death risk than those who received treatment of physician's choice (TPC) (HR 0.51; P < 0.01), with median OS of 10.0 and 4.8 months, respectively (81). In ATTAIN trial, a phase III study of NKTR 102 versus TPC in metastatic BC patients (82), the median PFS in BM patients of NKTR 102 and TPC was 3.9 and 3.3 months, respectively (HR, 0.59; 95% CI, 0.33-1.05; P =0.07), and the median OS in both the groups was nearly the same (7.8 months for NKTR 102, and 7.5 months for TPC group; HR=0.90; 95% CI, 0.61-1.33; P =0 .60) (83). The ATTAIN randomized clinical trial was not consistent with the positive OS benefit observed in BEACON trial (81,83).…”
Section: Treatment For Triple-negative Bcbm 41 Chemotherapymentioning
confidence: 92%
See 1 more Smart Citation
“…In the BEACON trial (a phase III trial), BCBM patients who received NKTR-102 treatment had a markedly lowered death risk than those who received treatment of physician's choice (TPC) (HR 0.51; P < 0.01), with median OS of 10.0 and 4.8 months, respectively (81). In ATTAIN trial, a phase III study of NKTR 102 versus TPC in metastatic BC patients (82), the median PFS in BM patients of NKTR 102 and TPC was 3.9 and 3.3 months, respectively (HR, 0.59; 95% CI, 0.33-1.05; P =0.07), and the median OS in both the groups was nearly the same (7.8 months for NKTR 102, and 7.5 months for TPC group; HR=0.90; 95% CI, 0.61-1.33; P =0 .60) (83). The ATTAIN randomized clinical trial was not consistent with the positive OS benefit observed in BEACON trial (81,83).…”
Section: Treatment For Triple-negative Bcbm 41 Chemotherapymentioning
confidence: 92%
“…In ATTAIN trial, a phase III study of NKTR 102 versus TPC in metastatic BC patients (82), the median PFS in BM patients of NKTR 102 and TPC was 3.9 and 3.3 months, respectively (HR, 0.59; 95% CI, 0.33-1.05; P =0.07), and the median OS in both the groups was nearly the same (7.8 months for NKTR 102, and 7.5 months for TPC group; HR=0.90; 95% CI, 0.61-1.33; P =0 .60) (83). The ATTAIN randomized clinical trial was not consistent with the positive OS benefit observed in BEACON trial (81,83).…”
Section: Treatment For Triple-negative Bcbm 41 Chemotherapymentioning
confidence: 92%
“…Etirinotecan pegol (NKTR-102) is a long-acting topoisomerase-I inhibitor used for patients with MBC and brain metastases. However, in the phase III ATTAIN randomized clinical trial, no statistically significant difference in survival outcomes was observed in patients treated with etirinotecan pegol and patients treated with chemotherapy of physician’s choice [ 147 ]. These findings are questionable [ 148 ] and further studies are needed.…”
Section: Breast Cancer Therapiesmentioning
confidence: 99%
“…To the Editor We read with interest the article by Tripathy et al reporting the results of the ATTAIN randomized clinical trial, which found no statistically significant difference in survival outcomes between treatment with etirinotecan pegol (EP) and chemotherapy of physician’s choice (CPC) in patients with breast cancer with brain metastases. Although this study is impressive, we have a few concerns and suggestions for this study.…”
mentioning
confidence: 99%
“…This study did not compare the size, number, and location of brain metastases between the 2 groups to control confounding factors. This study also did not report the comparison of objective response rate (ORR) between the EP and CPC groups.…”
mentioning
confidence: 99%